Compartmentalized effects of aging on group 2 innate lymphoid cell development and function. Issue 6 (20th August 2019) - D'Souza, Shanti S.; Shen, Xiaofei; Fung, Ivan T. H.; Ye, Longyun; Kuentzel, Marcy; Chittur, Sridar V.; Furuya, Yoichi; Siebel, Christian W.; Maillard, Ivan P.; Metzger, Dennis W.; Yang, Qi
Abstract: The effects of aging on innate immunity and the resulting impacts on immunosenescence remain poorly understood. Here, we report that aging induces compartmentalized changes to the development and function of group 2 innate lymphoid cells (ILC2), an ILC subset implicated in pulmonary homeostasis and tissue repair. Aging enhances bone marrow early ILC2 development through Notch signaling, but the newly generated circulating ILC2 are unable to settle in the lungs to replenish the concomitantly declining mature lung ILC2 pool in aged mice. Aged lung ILC2 are transcriptomically heterogeneous and functionally compromised, failing to produce cytokines at homeostasis and during influenza infection. They have reduced expression of Cyp2e1, a cytochrome P450 oxidase required for optimal ILC2 function. Transfer of lung ILC2 from young mice enhances resistance to influenza infection in old mice. These data highlight compartmentalized effects of aging on ILC and indicate that targeting tissue‐resident ILCs might unlock therapies to enhance resistance to infections and diseases in the elderly. Abstract : Aging is paradoxically associated with increased early ILC2 development in bone marrow but reduced cellularity and function of mature ILC2 in the lung. Diminished ILC2 responses contribute to increased susceptibility to influenza infection with aging.